RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI PELAYANAN MASYARAKAT BERBASIS WEBSITE DI WILAYAH RW 015 KELURAHAN TANJUNG PRIOK JAKARTA UTARA - Aditya Rizky (2022)
Providing a good quality of society is the hope for every service provider of public services. In practice, the correspondence service in the area of RW 015, Kelurahan Tanjung Priok, North Jakarta, still applies a work system that takes a long time, where to get a letter of application, local residents must first come to the RW office and then submit an application. This system is designed using Laravel as a development framework, and the system development method used is waterfall by applying the Unified Modeling Language (UML) as an information system design model. The result of this research is the creation of a web-based public service administration information system that is able to carry out the community service process quickly, and can record the administration that has been done. From the results of the system evaluation, the application process for using this system is faster, approximately 20 to 30 minutes of service than the conventional process.